Predictors and risk factors for admission to critical care in cervicofacial infections: a Maxillofacial Trainee Research Collaborative (MTReC) study. Issue 1 (January 2023) - ES Dawoud, B; Kent, S.; Henry, A; McDonald, C; Kyzas, P.; McCaul, J.; ,; Java, Kapil; Keria, Ashwin; Ng, Teresa; Kawalec, Alex; Gowrishankar, Siddharth; et al.
Abstract: Cervicofacial infections carry significant morbidity. Patients present on a broad spectrum of severity, with some requiring outpatient management and others admission to higher level care. Recognition of risk factors is helpful in decision making regarding the need for admission to higher level care. Prospective data were captured on 1002 patients in 25 centres across 17 regions of the United Kingdom (UK) by the Maxillofacial Trainee Research Collaborative (MTReC). Patients admitted to critical care were compared with those who received ward-level care. Multivariate and receiver operating characteristic curve analyses were used to identify predictors for critical care admission. Our results show that the best predictor for critical care admission is the presence of three or more features of airway compromise (AUC 0.779), followed by C-reactive protein (CRP) >100 mg/L (OR 2.70; 95% CI 1.59 to 4.58; p < 0.005), submandibular space involvement (OR 3.82; 95% CI 1.870 to 7.81; p = 0.003), white cell count (WCC) >12 × 10 9 / dl (1.05; 95% CI 1.01 to 1.10; p = 0.03), and positive systemic inflammatory response syndrome criteria (OR 2.78; CI 1.35 to 5.80; p = 0.006). Admission to critical care is multifactorial, however, the presence of three or more features of airway compromise is the best predictor. Awareness of this alongside other key clinical findings in cervicofacial infections may allow for the early recognition of patients who may require escalation to critical care.